Marine Tourism Potential in Pangandaran Regency - Indah Kurniasih; Atikah Nurhayati; Lantun Paradhita Dewanti; Achmad Rizal (JURNAL PERIKANAN DAN KELAUTAN, 2020)
Tourism sector in Pangandaran Regency is an important sector that contributes regional income. One of the famous types of tourism in Pangandaran Regency is marine tourism. Conditions and geographical location of Pangandaran Regency which has 91 km coast line makes Pangandaran as one of the favorite marine tourism destinations in West Java. This conditions allows marine tourism to become a leading sector that has potential in terms of tourism attraction and economic valuation. Based on that condition, this study was conducted to find out the economic potential and the factors that influence numbers of tourist visits to marine tourism in Pangandaran Regency. A total of 96 tourist respondent were asked to answer several questions related to the study that was held at five marine tourism locations in Pangandaran Regency (Karapyak Beach, Pangandaran Beach, Batuhiu Beach, Batukaras Beach and Madasari Beach). This study began in September 2019 until July 2020. Based on the results of the study, it is known that marine tourism in Pangandaran Regency 3A potential (attraction, accessibility and amenities/accomodation). The findings indicated that from six factors under study, the most influential factors in the marine tourism demand in Pangandaran Regency are income, travel expense and distance travelled. Consumen surplus based on the individual travel cost method (TCM) amounting to 13,354 IDR per individual per visit and then obtained the estimated economic value of tourism is 51,763,207,799 IDR